Investigations of hypoxia‐induced deoxyhemoglobin as a contrast agent for cerebral perfusion imaging. Issue 3 (29th October 2022) - Sayin, Ece Su; Schulman, Jacob; Poublanc, Julien; Levine, Harrison T.; Raghavan, Lakshmikumar Venkat; Uludag, Kamil; Duffin, James; Fisher, Joseph A.; Mikulis, David J.; Sobczyk, Olivia
Abstract: The assessment of resting perfusion measures (mean transit time, cerebral blood flow, and cerebral blood volume) with magnetic resonance imaging currently requires the presence of a susceptibility contrast agent such as gadolinium. Here, we present an initial comparison between perfusion measures obtained using hypoxia‐induced deoxyhemoglobin and gadolinium in healthy study participants. We hypothesize that resting cerebral perfusion measures obtained using precise changes of deoxyhemoglobin concentration will generate images comparable to those obtained using a clinical standard, gadolinium. Eight healthy study participants were recruited (6F; age 23–60). The study was performed using a 3‐Tesla scanner with an eight‐channel head coil. The experimental protocol consisted of a high‐resolution T1‐weighted scan followed by two BOLD sequence scans in which each participant underwent a controlled bolus of transient pulmonary hypoxia, and subsequently received an intravenous bolus of gadolinium. The resting perfusion measures calculated using hypoxia‐induced deoxyhemoglobin and gadolinium yielded maps that looked spatially comparable. There was no statistical difference between methods in the average voxel‐wise measures of mean transit time, relative cerebral blood flow and relative cerebral blood volume, in the gray matter or white matter within each participant. We conclude that perfusion measures generated with hypoxia‐induced deoxyhemoglobin are spatially and quantitatively comparable to those generated from a gadolinium injection in the same healthy participant. Abstract : The exploration of hypoxia‐induced dOHb as a noninvasive contrast agent for cerebral perfusion imaging with magnetic resonance imaging.